The impact of physical activities on adolescents’ rule consciousness: the chain mediation effect of friendship quality and emotional intelligence - Peng, Jiahui; Cao, Li; Zhou, Deqiao (Frontiers in Public Health, 2025)
IntroductionWith the increasing emphasis on the development of adolescents’ character and behavior in modern society, how to effectively cultivate adolescents’ rule awareness has become a pressing issue in the field of education. Despite the increasing emphasis on developing adolescents’ character and behavior, educators face significant challenges in cultivating rule awareness. Traditional educational practices often fall short in integrating physical activity with socio-emotional learning, and they struggle to capture the complex dynamics influencing rule adherence. Rule awareness is not only a crucial foundation for social behavioral norms but also has a profound impact on adolescents’ personal growth and social adaptability. This study investigates the effect of physical activity on adolescents’ rule awareness and reveals the chain mediation effects of friendship quality and emotional intelligence.MethodsTo explore the relationship between physical activity and adolescents’ rule awareness and analyze the mediating and chain mediating roles of friendship quality and emotional intelligence, a questionnaire survey was conducted with 612 adolescents aged 8–16. Data were analyzed using SPSS 27.0 and PROCESS 4.0 for correlation analysis, regression analysis, and mediation effect testing.ResultsPhysical activity significantly and positively predicted adolescents’ rule awareness. Friendship quality and emotional intelligence played independent mediating roles and formed a chain mediation effect in this process. The study’s findings reveal the complex mechanisms through which physical activity, friendship quality, and emotional intelligence influence adolescents’ rule awareness, providing theoretical foundations and practical insights for further investigating important factors affecting adolescents’ rule awareness, effectively curbing rule violations, and continuously strengthening rule awareness development.ConclusionTo further enhance adolescents’ rule awareness and maintain social order and stability, both schools and society should create a favorable sporting environment and reasonably increase the amount of physical activity among adolescents.